A new governance framework to safeguard the European Green Deal - Jean Pisani-Ferry; Simone Tagliapietra; Georg Zachmann (Bruegel, 2023)
With the European Green Deal, the European Union adopted ambitious climate targets and a wave of legislation to reach them. But implementation will be politically challenging, in particular because the Green Deal has not upgraded the EU's energy and climate governance framework. We propose five priorities for governance reform: 1. All emissions should be made subject to emissions trading. By 2030, separate emissions trading systems (ETS) will cover industrial emissions and buildings/transport emissions, representing three-quarters of all territorial emissions. A third ETS should be created for sectors not yet covered and the emission control mechanisms should be unified by 2040. 2. Preparations should start for an EU Green Investment Plan. This should ensure that after pandemic recovery funding ends in 2026, EU green grants remain at least at the current level of exteuro50 billion per year (0.3 percent of GDP). Making up the annual shortfall would require new EU resources amounting to exteuro180 billion between 2024 and 2030, but this will be important to tackle the political and distributional problems the EU will increasingly face. In addition, currently discussed EU economic governance reforms should be amended to allow countries with public debt exceeding 60 percent of GDP but with sustainable public finances to reduce debt at a slower pace, on the condition that additional emissions-reducing investments are made. 3. A European Energy Agency should be established. This would provide unbiased reference points for policy evaluation and preparation. It would not have decision-making powers but would gather and make available data for decision-making, maintain open modelling tools, and independently assess EU and member-state policies. 4. Energy and climate governance should be elevated to heads of state and government level to increase policy coordination and political ownership. Special European summits would be organised at least once a year, with preparations done by EU energy and climate sherpas. 5. Transmission network development and operation should be driven by European cost minimisation. An European independent network system operator would be able to ensure that existing cross-border transmission is used optimally, also with a view to fostering investment.
Keywords: 330